1990
DOI: 10.1111/j.1365-3091.1990.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and facies model of a macrotidal sand‐bar complex, Cobequid Bay—Salmon River Estuary (Bay of Fundy)

Abstract: The 40‐km‐long, Cobequid Bay—Salmon River estuary has a maximum tidal range of 16·3 m and experiences limited wave action. Sediment, which is derived primarily from areas seaward of the estuary, is accumulating faster than the high‐tide elevation is rising, and the system is progradational. The deposits consist of an axial belt of sands, which is flanked by mudflats and salt marshes in the inner half of the estuary where a funnel‐shaped geometry is developed, and by erosional or non‐depositional foreshores in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(95 citation statements)
references
References 49 publications
(94 reference statements)
3
82
0
10
Order By: Relevance
“…It is common, tides produce water currents in settings of marine embyments (e.g. Knight 1980, Dalrymple et al 1990). Finally, storms are not speculated to have forme the currents because to pure occurrence of typical storm sedimentary structures (e.g.…”
Section: Sedimentary Model Of the Tøenice Formationmentioning
confidence: 99%
“…It is common, tides produce water currents in settings of marine embyments (e.g. Knight 1980, Dalrymple et al 1990). Finally, storms are not speculated to have forme the currents because to pure occurrence of typical storm sedimentary structures (e.g.…”
Section: Sedimentary Model Of the Tøenice Formationmentioning
confidence: 99%
“…Water discharge greater than 60,000 m 3 /s, increase the water surface gradient and the sediment carrying capacity in the estuary (Yang et al, 1999). Estuarine sedimentation and landform features have been observed and studied in various settings around the world, including the Thames Estuary, Cobequid Bay, and the Bay of Fundy (Dalrymple and Rhodes, 1995;Knight, 1980;Dalrymple et al, 1990), as well as Chesapeake Bay (Ludwick, 1974) and Moreton Bay (Harris et al, 1992). These studies found that tidal bars in all these estuarine settings are important sedimentary features.…”
Section: Formation Mechanism Of the Yangtze River Estuarymentioning
confidence: 99%
“…In particular marsh deposits are characterized by the recognition of siltypelitic sediments rich in organic matter with lesser amounts of sandstone, and levels of calcareous levels and abundant root molds in compact layers (Lander et al, 1990). This is due to the fact that marshes are confined to areas above the average elevation of water (Dalrymple et al, 1990) and poor drainage on these elevated areas within the flats favors the preservation of organic material. Because they are reducing environments, wetlands are conducive to the development of soils with gley horizons, which is why mottling is common and abundant (Aslan and Autin, 1998).…”
Section: Facies Association: Intertidal Flats (Itf)mentioning
confidence: 99%
“…The presence of parallel lamination in this association demonstrates the migration of low-amplitude waves on flat surfaces by currents that reached speeds of 2 m/sec and depths less than 2-3 m or the combination of storm events and tidal action (Dalrymple et al, 1990;Fielding, 2006). The varied bedforms and the stability field of these structures is a function of changes in the speed and size of grain for a constant water depth and temperature (Fielding, 2006).…”
Section: Facies Association: Subtidal Flats (Stf)mentioning
confidence: 99%
See 1 more Smart Citation